Peran Psikologi Manajemen dalam Organisasi: Tinjauan Sistematis terhadap Inovasi, Kinerja, dan Efektivitas Manajemen (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
The development of organizations in the modern era demands the integration of psychological aspects into management practices to enhance effectiveness, innovation, and performance. Organizational psychology and management psychology are becoming increasingly important in addressing the dynamics of change and the complexity of the work environment. This study aims to identify and synthesize the role of psychology in organizational management and answer the research questions: how management psychology contributes to organizational innovation and performance, as well as key themes and existing research gaps. The method used was a literature review with a qualitative approach. Data was obtained from the Google Scholar and Publish or Perish (PoP) databases using keywords related to organizational psychology, innovation, and management. A total of 16 articles were identified and then selected to seven relevant articles for analysis. The results of the study identified three main themes: the role of psychology in management effectiveness, the influence of psychological factors on innovation and performance, and the contribution of management psychology in addressing organizational change. Overall, psychological factors have been shown to play a significant role in improving organizational performance and competitiveness. Future research is recommended to develop an integrative model that comprehensively combines various aspects of management psychology in different organizational contexts.